2012
DOI: 10.1007/s00038-012-0384-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of exposure to occupational risks during pregnancy in Spain

Abstract: Our data suggest that working conditions of pregnant women may need increased control in Spain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…The same research group in Spain searched for risk factors during pregnancy using self-reports, which are the predominant method to report psychosocial risks. The results of these investigations revealed that the prevalence of the psychosocial risks was, on average, higher than any other chemical, physical or biological factors [33] . Several researchers studied the psychological stress in a specific pathology, for example, in diabetes.…”
Section: Job Occupation and Psychologi-cal Stressmentioning
confidence: 88%
“…The same research group in Spain searched for risk factors during pregnancy using self-reports, which are the predominant method to report psychosocial risks. The results of these investigations revealed that the prevalence of the psychosocial risks was, on average, higher than any other chemical, physical or biological factors [33] . Several researchers studied the psychological stress in a specific pathology, for example, in diabetes.…”
Section: Job Occupation and Psychologi-cal Stressmentioning
confidence: 88%
“…In one such study, Dr Martine Vrijheid analyzed the effects of prenatal chemical exposure to suspected obesogens (persistent organic pollutants, BPA, and cigarette smoke) by tracking their effects over the growth trajectory from prenatal growth to early postnatal growth and obesity in young children (unpublished data). In a Spanish birth cohort study, more than 2000 mother-child pairs were recruited in the first trimester of pregnancy (Garcia et al, 2012). Vrijheid stated that DDE and HCB did not affect prenatal growth (birth weight) but was associated with rapid postnatal growth and subsequent overweight in early childhood.…”
Section: Session Vii: National and Synthetic Birth Cohortsmentioning
confidence: 99%
“…Relatively few studies have assessed the health of female farmworkers distinctly from their male counterparts or the impact of agricultural work-related tasks on pregnancy outcomes. Besides pesticide exposure, other occupational risk factors that are of concern for pregnant women include ergonomic tasks involving repetitive motion, heavy lifting, frequent bending and prolonged standing and prolonged work in high temperatures with limited access to drinking water [11,12,13,14,15,16]. …”
Section: Introductionmentioning
confidence: 99%